2015
DOI: 10.1186/s13104-014-0961-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in children with asthma: a systematic review and meta-analysis

Abstract: BackgroundEpidemiologic studies suggest an association between vitamin D deficiency and atopic diseases, including asthma. The objective of this study was to systematically review the benefits and harms of vitamin D supplementation in children with asthma.MethodsWe used standard Cochrane systematic review methodology. The search strategy included an electronic search in February 2013 of MEDLINE and EMBASE. Two reviewers completed in duplicate and independently study selection, data abstraction, and assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…In addition, children are sedentary with more screen time and less time spent outdoors, have a higher BMI, both of which have been associated with asthma . Together, the composite investigation of these myriad factors and the influence of Western lifestyle will allow an improved understanding of the mechanisms that underlie the inconclusive results of vitamin D supplementation . Hence, future studies are needed to better define the individual or combined role of inflammation, metabolic dysregulation, gut microbiome, and vitamin D bioavailability in the association between vitamin D deficiency and pediatric asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, children are sedentary with more screen time and less time spent outdoors, have a higher BMI, both of which have been associated with asthma . Together, the composite investigation of these myriad factors and the influence of Western lifestyle will allow an improved understanding of the mechanisms that underlie the inconclusive results of vitamin D supplementation . Hence, future studies are needed to better define the individual or combined role of inflammation, metabolic dysregulation, gut microbiome, and vitamin D bioavailability in the association between vitamin D deficiency and pediatric asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings define a new mechanism that may underlie pediatric obesity‐related asthma, a mechanism that may be amenable to supplementation and dietary modification. Given the inconclusive results on the effectiveness of vitamin D supplementation in improving asthma outcomes and pulmonary function, perhaps additional analyses of these studies based on the participant BMI may identify differential effects of vitamin D supplementation among obese children with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many RCTs of vitamin D supplementation to improve asthma control and exacerbations have been completed and these studies have reported a mixture of positive and negative results. However, several meta-analyses show that vitamin D supplementation significantly reduced the rate of severe exacerbations in patients with asthma [109][110][111][112][113]. Whether these effects are only observed in patients with vitamin D deficiency, as was shown in COPD, is less clear since only two studies performed subgroups analysis, showing conflicting results [112,113].…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%
“…In our search for SRs on vitamin D and asthma risk, we identified 18 articles [38,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] of which 10 reported data on cohort studies [67][68][69][70][71][72][73][74][75][76] and eight reported data on RCTs [38,[77][78][79][80][81][82][83] ( Supplemental Table S2-S5 and Figure S1). Out of the 18 SRs, 14 were restricted to children [67,[69][70][71][72][73][74][75][76][77][78][79]…”
Section: Resultsmentioning
confidence: 99%